Patient cost sharing: Reforms without evidence. Theoretical considerations and empirical findings from industrialized countries - Jens Holst (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2010)
International health service research reveals a uniform tendency in practically all industrialised countries: an increasing shift of costs from solidarity-based financing to private households. Legislators and advisors usually justify this policy through the need to encourage cost-consciousness and especially individual responsibility. Economists consider cost-sharing in health care to be necessary to prevent abuse of the welfare state. They expect user charges and co-payments to motivate a more rational utilisation of health care and, thus, the financial stabilisation of health systems. Many politicians and economists base their assumptions about the health market on the theorem of demand-side moral hazard. This model transforms patients into rational utility maximisers consuming services beyond their needs thereby causing welfare losses to society as a whole. Moral hazard in health insurance belongs to the standard repertoires of economic textbooks. The present study analyses the extensive theoretical and empirical literature on patient cost-sharing published during the last forty years. The results show that persuasive evidence for demand-side moral hazard is still lacking. Furthermore, the claimed empiricism turns out to be inappropriate for providing evidence. Science health service research and clinical studies instead suggest that health insurance beneficiaries are not aiming to abuse the health system. In fact, introducing patient cost-sharing seems to endanger proper health care since it deters the sick from claiming benefits. The idea of rational use transpires to be out of touch with reality. After a systematic in-depth review of current research on the topic, the author concludes that moral hazard in health insurance is a bogey of academic economic theory. Adequate reality-based evidence for implementing patient user fees and co-payments is lacking. In view of the detrimental effects on health service utilisation, he advises cancelling existing co-payment arrangements and abandoning cost-sharing policies. – – Die internationale Gesundheitssystemforschung zeigt in praktisch allen Industrieländern einen einheitlichen Trend auf: die zunehmende Verlagerung der Kosten von der solidarischen Finanzierung auf die privaten Haushalte. Gesetzgeber wie Berater begründen dies üblicherweise mit der Stärkung von Kostenbewusstsein und vor allem der Eigenverantwortung. Wirtschaftswissenschaftler betrachten Selbstbeteiligungen in der Gesundheitsversorgung als notwendig, um dem Missbrauch der Solidargemeinschaft entgegenzuwirken. Von Gebühren und Zuzahlungen erwarten sie eine vernünftigere Inanspruchnahme der Gesundheitsleistungen und eine finanzielle Stabilisierung der Systeme. Die Sicht vieler Politiker und Wirtschaftsexperten auf den Gesundheitsmarkt ist durch das Theorem des versichertenseitigen Moral Hazard geprägt. Dieses Modell macht Krankenversicherte zu rationalen Nutzenmaximierern, die zum eigenen Vorteil über den Bedarf hinaus Leistungen in Anspruch nähmen und dadurch gesamtgesellschaftliche Wohlfahrtsverluste verursachten. Moral Hazard in der Krankenversicherung gehört zum Standard-Repertoire ökonomischer Lehrbücher. Die vorliegende Arbeit wertet die umfangreiche Literatur über Ansätze und Versuche der Kostenbeteiligung von Patienten aus, die in den letzten vier Jahrzehnten erschienen ist. Dabei stellt sich heraus, dass belastbare Belege für das Moral-Hazard-Verhalten von Versicherten bzw. Patienten bisher fehlen und die üblicherweise angeführte Empirie für den Nachweis ungeeignet ist. Gesundheitswissenschaftliche, versorgungsbezogene und klinische Studien legen vielmehr nahe, dass die Versicherten das System nicht ausnutzen wollen oder können. Die Einführung von Kostenbeteiligungen für Patienten scheint eher die bedarfsgerechte Versorgung zu gefährden, weil sie Kranke von der Inanspruchnahme abhalten. Die Vorstellung von der rationalen Nutzung des Gesundheitswesens entpuppt sich als realitätsfremd. Nach gründlicher Auswertung des Forschungsstandes kommt der Autor zum Schluss, dass Moral Hazard in der Krankenversicherung ein Popanz der akademischen Wirtschaftstheorie geblieben ist. Für die Einführung von Kostenbeteiligungen für Patienten fehlt es an hinreichender realitätsbasierter Evidenz. In Anbetracht der schädlichen versorgungspolitischen Effekte erscheinen die Rücknahme aller Patientenzuzahlungen und der Verzicht auf Selbstbeteiligungen geboten.
Keywords: 300; Selbstbeteiligung; Patienten; Deutschland